Characteristics of Multiparous Delivering Mothers with Perineal Rupture - Grevillea Julce Peday; Hamdiah Ahmar; Jan Pieter E. A. Kambu; Risna Yunita Asmin; Ayu Kurnia Anggraeni (International Journal Of Health Science, 2023)
Perineal rupture is a cause of postpartum bleeding within the first 24 hours. Hemorrhage is the primary cause of maternal mortality in Indonesia; birth canal trauma is the second leading cause of bleeding after uterine atony. The higher the mother's parity, the more reproductive functions tend to decline. The purpose of this research is to understand the characteristics of multiparous delivering mothers with perineal rupture. This study employs a quantitative descriptive approach. Data collection is derived from secondary sources obtained from medical records in the Delivery Room of the Sorong Regency General Hospital. The study was conducted in June 2023. The sample comprises all multiparous delivering mothers who experienced perineal rupture and met the inclusion criteria in the Delivery Room of the Sorong Regency General Hospital, totaling 242 delivering mothers from January to December 2022. The sampling technique used is Purposive Sampling. Univariate analysis is employed to calculate the frequency distribution, including the age of the mothers, education, occupation, perineal rupture, and newborn baby's weight. The majority of multiparous delivering mothers are between 20-35 years old, totaling 195 individuals (80.6%). The respondents' educational level is predominantly high school (SMA), totaling 124 individuals (51.2%). Non-working mothers account for 166 individuals (68.6%). The most frequent occurrence of perineal rupture is categorized as Level 1, totaling 81 individuals (33.5%). Newborns with the largest birth weight fall into the Normal category (2500-4000 grams), totaling 210 individuals (86.8%). Perineal rupture is one of the factors contributing to postpartum hemorrhage, which can lead to maternal death if not properly managed.